Implementasi dan Analisis Metode Hierarchical Token Bucket dan Per Connection Queue pada Jaringan Multi Protocol Label Switching Traffic Engineering untuk Layanan Voice over Internet Protocol - Anggayasti Ariane Zuqhra; Nur Rohman Rosyid (Maranatha University Press, 2018)
In growing industrial era, communication technology through IP network is becoming vital for supporting enterprises productivities. One of high performance communications that is used nowadays is VoIP (Voice over Internet Protocol). VoIP is able to do remote communication without spending high fees. Alongside with high requirements of transmitting and receiving data packet in network, bandwidth management is necessary, so that the decreasing of network performance will not occur. Bandwidth management methods supported by MikroTik RouterOS are HTB (Hierarchical Token Bucket) and PCQ (Per Connection Queue). This research compared HTB and PCQ methods for stabilizing VoIP based on MOS (Mean Opinion Score) parameter and QoS (Quality of Service) parameters such as delay, jitter, throughput, and packet loss using MikroTik devices. In this research, VoIP was tested in MPLS-TE (Multi Protocol Label Switching Traffic Engineering) network. The advantages of TE in MPLS combined with bandwidth management method are maximizing the resources and services in a network and resulting good QoS. The result of this research is that the best QoS and MOS values are from MPLS-TE network using HTB method in normal condition and full bandwidth. In normal condition, the value of delay is 16,02 ms, jitter is 0,00000004 ms, 0% for packet loss, and 146,4 kbps for throughput. When bandwidth is full, delay is 40,567 ms, 0,000000073 ms for jitter, packet loss is 12,667%, and throughput is 58,2 kbps.